Database Management System Pada Perusahaan - Sucinta Tri Nurhayati; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2023)
In a company using all the roles of technology in its application to increase productivity. One of them is the database. This journal aims to find out that the database acts as a collection of information data that is systematic, checked, and processed to obtain more accurate information. The database also functions as a grouping of data to facilitate its identification of data later. The software used to process and use databases is the Database Management System (DBMS). The DBMS system can later provide optimal information for decision making within a company.